Exploration of professional identity development of PK-12 educational leaders in a public school system - Rector, Shanna L. (Kansas State University, 2024)
Educational leaders in a public school system contribute to the success of students and impact the learning environment. Discovering ways to support these important professionals is a worthwhile endeavor. An educational leader's professional identity is significant to their performance and serves as a compass to guide decisions and actions. Supporting the professional identity development of educational leaders is a crucial way to contribute to the journey and effect of the leader during their career. This basic qualitative study explored how educational leaders develop their professional identity and the relationship of professional standards to their professional identity. The study design included interviewing administrators from a public school system that experienced at least one career move within the same district to a leadership role, recognizing them as an educational leader. Employment of a pilot study was included to strengthen the design of the exploratory study data collection methodology. In conjunction with the semi-structured interview data collection, additional data was collected in the form of participant created concept maps. The conceptual framework served as a guide during the data collection and analysis process to orient the influencing constructs and descriptions of educational standard intersections to the development of professional identity. Five themes were identified: 1) capacity creating opportunities; 2) drivers toward the mission; 3) establishing desired culture; 4) influencing socializing agents; and 5) living aspired dispositions. The study results served to enhance the ability to inform practices of support for educational leaders focused on: supporting and growing current leaders through dialogue and access, infusing the repository of professional standards as a resource to enhance expertise, and harnessing the power of leaders within the system as developers of the professional identity of the next generation of educational leaders.
Keywords: Professional identity; Educational leaders